Effects of match location, quality of opposition, match outcome, and playing position on load parameters and players' prominence during official matches in professional soccer players - Goncalves, Luiz Guilherme Cruz (2021)
Purpose. This study aimed to investigate the effects of match location, quality of opposition, match outcome, and playing position on internal load (IL), external load (EL), and interpersonal interactions in professional soccer players. Also, the relationships between load parameters and interpersonal interactions were measured. Methods. Fourteen matches from 16 Brazilian professional players were analysed. IL was obtained through the rating of perceived exertion. EL was quantified with the Global Positioning System (e.g., high-intensity running [HIR]). Interpersonal interactions were measured by network analysis using completed passes between teammates (n = 2845). Results. Higher values of match IL and HIR were observed in home vs. away matches (p = 0.02). Players presented greater running outputs and number of networks that a player controlled in matches against strong vs. weak opponents (p < 0.05). When the players won the matches, higher running demands and proximity to the teammates (i.e., closeness centrality) were demonstrated than when they drew or lost (p < 0.05). Reduced values of IL, EL, and closeness centrality were observed in the forwards compared with the other positions (p < 0.05). The distance covered per minute in HIR was large and associated with closeness centrality and eigenvector (r = 0.55; p < 0.001). Conclusions. The results indicate that load parameters and interpersonal interactions are influenced by the considered independent variables.